Government and economics: An emerging field of study - David D. Li; Eric Maskin (Journal of Government and Economics (JGE), 2021)
In this paper, we discuss the field of government and economics, an emerging body of work that aims to better understand government's role, incentives and behavior in a modern market economy, as well as how government actions shape the economy's performance. In the first part of the paper, we present evidence that the size and scope of government in market economies have grown much larger since the industrial revolution. We then briefly examine particular periods in the histories of the U.S., Germany, Japan, South Korea, and China when these countries' governments played an especially vigorous role in promoting rapid economic growth. We also provide statistical evidence that, across countries, more robust market-supporting behavior from governments is associated with higher per capita income and faster growth. The second part begins with a review of existing areas of economic research suggesting that, so far, the discipline has neglected some significant questions concerning government as an active player in a modern market economy. Finally, we propose a number of possible future research topics that we think are tailored for the new field of government and economies.
Keywords: 330